Giving honey as a complementary therapy in the prevention and treatment of Diabetes mellitus wounds in RT 9 RW 10 Kebayo - Andriana, Nana; Fajriyah Nur Afriyanti; Diana Rhismawati Djupr; Dewi Susanti (ABDIMASNU: Jurnal Pengabdian kepada Masyarakat, 2025)
One alternative treatment for diabetic wounds is using honey therapy.Honey has sufficient water and moisture content so that it does notsupport bacteria to grow and multiply.A survey conducted in the Kebayoran Lama sub-district area, there arestill DM patients who experience diabetic wounds and undergotreatment using water and betadine, 0.9% NaCl solution, pure honey, andNebacetin powder. This program also supports This effort hassucceeded in increasing the knowledge and skills of the community incarrying out DM wound care.The number of people who participated in the study was 70. TheRT 9 area. Data collection used a blood sugar observation sheet beforeand after DM wound care. From these results, it can be concluded thatall residents of RT 9 can carry out DM wound care independently at homeusing topical pure honey.